Diagnostic challenges of indolent peripheral T cell lymphoma: A case report and literature review. Issue 42 (16th October 2020) - Lee, Jisoo; Park, Kyeoungseo; Kim, Kyoung Ha; Bang, Hae In; Yoon, Seug Yun; Choi, In Ho
Abstract: Introduction: Peripheral T cell lymphoma, not otherwise specified (PTCL-NOS) is a heterogeneous group of mature T cell lymphomas which do not correspond to any specific subtype of mature T-cell lymphoma in current classifications. Some researchers have suggested that PTCL with low Ki-67 labeling index should be classified as indolent PTCL Patient concerns: A 58-year old man diagnosed with alcoholic fatty liver 3 months prior complained of tenesmus and abdominal distension. Colonoscopy of the small and large intestines revealed multiple polyps, which were histologically diagnosed as lymphoid hyperplasia. One month later, he re-visited with a weight loss of 3 to 4 kg over 2 months. Radiologic examination revealed numerous small, homogenous, hypovascular lymph node enlargement in the para-aortic, mesenteric, and both inguinal areas, suggesting malignant lymphoma. Diagnosis: Laparoscopic biopsy of an omental lymph node was performed, which was histologically confirmed as PTCL-NOS. Interventions: The patient was administered 3 cycles of cyclophosphamide, doxorubicin, vincristine, and prednisone, but his general condition did not improve. Therefore, treatment was changed to ifosfamide, carboplatin, and etoposide -dexamethasone (4 cycles) followed by allogeneic stem cell transplantation. Outcome: Even after allogeneic stem cell transplantation, fluorodeoxyglucose uptake in his abdominal lymph nodes and small bowel in positron emission tomography- computed tomography persisted at a Deauville score of 4. The patient has been followed-up for 2 years without progression. Conclusion: These indolent PTCLs histologically show diffuse infiltrated small lymphoid cells with low KI-67 labeling index and have a relatively good prognosis, although the epidemiology and pathogenesis are not fully elucidated. We report a case of indolent PTCL with cytogenetic abnormalities and poor response to chemotherapy, along with a brief review of the literature.